PENGARUH UKURAN PERUSAHAAN, KEBIJAKAN HUTANG, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA - Pratiwi, Niken Indah; Farida, Lena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of Firm Size, Debt Policy, and Dividend Policy on Corporate Value in Manufacturing Companies Listed on Indonesia Stock Exchange (IDX). The ratio used to measure firm size as independent variable is Natural Logarithm of Total Asset and Natural Logarithm and Total Sales. The ratio used to measure debt policy is Debt to Equity Ratio (DER) and Debt to Total Asset Ratio (DAR), while the ratio used to measure dividend policy is Dividend Payout Ratio (DPR). Meanwhile, the ratio used to measure Company Value is Price Book Value (PBV) and Price Earning Ratio (PER). The method used to observe the effect of corporate measurement, debt policy, and dividend policy on firm value is by using multiple linear regression.Data used in this research are secondary data, financial report and annual report annual report. The data listed on the Indonesia Stock Exchange (IDX) for 3 years from 2012 to 2014. Sampling is done by purposive sampling, which is used is 16 companies. Data analysis using multiple linear regression analysis, t test, f test and coefficient of determination test. Data analysis using multiple linear regression analysis with SPSS 21.The result of the analysis shows that firm size variable does not affect the value of manufacture company of research sample that listed in Indonesia Stock Exchange. The debt policy variable does not affect the value of the manufacturing company of the research sample listed on the Indonesia Stock Exchange, and the dividend policy variable does not affect the value of the manufacturing company of the research sample listed on the Indonesia Stock Exchange. The result of simultaneous research shows that there is no influence from firm size variable, debt policy, and dividend policy on the value of manufacturing company of research sample listed in Indonesia Stock Exchange (IDX).Keywords: firm size, debt policy, dividend policy, corporate value